Strategi Guru PAI dalam Menanamkan Akhlak Mulia di SMK Negeri 6 Surakarta - Muhammad Fathur Rohman; Dartim Dartim (Jayapangus Press, 2026)
Character education in vocational high schools faces the challenges of vocational curriculum pragmatism and digital disruption in the Society 5.0 era, triggering moral degradation. This study aims to explore the operational strategies of Islamic Religious Education teachers in instilling noble character within the vocational ecosystem of SMK Negeri 6 Surakarta. A qualitative approach with a phenomenological descriptive design was employed through in-depth interviews, participatory observation in practice laboratories and classrooms, and documentation studies. Subjects were selected using a purposive sampling technique, including religious teachers, the vice principal, and students. Data were analyzed using the Miles and Huberman interactive model and validated through source and technique triangulation. Findings indicate a fundamental axiological paradigm reorientation, prioritizing adab over technical achievements. These strategies are operationalized through authentic personal role modeling or uswah hasanah, proactive pedagogical visits to laboratories to integrate trustworthiness with industrial standards, and communal habituation through spiritual organizations. Cross-disciplinary synergy with vocational teachers strengthens character building, despite constraints from high gadget usage that degrades communication ethics. This humanistic approach transforms student behavior evolutionarily from pseudo-compliance to intrinsic spiritual awareness in worship and socializing. In conclusion, character formation in the vocational ecosystem absolutely requires educators affective touch and tangible role modeling, which cannot be replaced by artificial intelligence technology.